Actual partial pressure of Se vapor in a closed selenization system: quantitative estimation and impact on solution-processed chalcogenide thin-film solar cells. Issue 17 (14th March 2016) - Han, Jeong Hyeob; Rehan, Shanza; Moon, Dong Gwon; Cho, Ara; Gwak, Jihye; Yoon, Kyung Hoon; Ahn, Seung Kyu; Yun, Jae Ho; Eo, Young Joo; Ahn, SeJin
Abstract : The actual Se partial pressure ( P Se ) was quantitatively estimated and its impact on the solution-processed CuInSe2 device was investigated. Abstract : One of the most important experimental factors in selenization, in which a precursor material is annealed at high temperature with Se vapor or gas to form chalcogenide light-absorbing layers, is the partial pressure of the Se vapor or gas ( P Se ). Although it is generally believed that the P Se should be sufficient to induce enhanced grain growth in the final film, the quantitative estimation of P Se has rarely been reported, and a detailed physical understanding of how the characteristics of absorber films and corresponding devices are affected by P Se is still far from clear. We performed a systematic study to address these P Se -related issues on solution processed CISe2 (CISe) thin films and solar cells. Based on a gas pressure equilibration model, we quantitatively estimated the actual P Se value and used this model to gain insight into how the initial experimental conditions of the Se level or background pressure influenced the actual P Se . It was found that the actual P Se varied significantly differently in an unexpected way: P Se did not vary linearly with the initial amount of Se and the trend of variation was significantly affected by the background pressure. The device parameter of the solution processed CISe solar cells that was primarily affected by P Se was the shunting, which is interpreted by the morphological differences of the absorber films grown under different P Se conditions.